2012
DOI: 10.1021/jp300861m
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of Single Vacancies in Rippled Graphene

Abstract: Using first-principles calculations, the dependence in the properties of the monovacancy of graphene under rippling controlled by an isotropic strain was determined, with a particular focus on spin moments. At zero strain, the vacancy shows a spin moment of 1.5 μ B that increases to ∼2 μ B when the graphene is in tension. The changes are more dramatic under compression in that the vacancy becomes nonmagnetic when graphene is compressed more than 2%. This transition is linked to the structural changes that occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
60
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 49 publications
6
60
2
Order By: Relevance
“…Santos et al 22 studied graphene with single vacancy and found tensile-strainenhanced spin moment. In contrast to graphene, V S2 -and V Mo -MoS 2 have no magnetism found till strain induces a semiconductor-metal transition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al 22 studied graphene with single vacancy and found tensile-strainenhanced spin moment. In contrast to graphene, V S2 -and V Mo -MoS 2 have no magnetism found till strain induces a semiconductor-metal transition.…”
Section: Resultsmentioning
confidence: 99%
“…The idea of applying strain arises from the following considerations: first, the magnetism found in the defected graphene may arise partly from an itinerant origin 2,5,22 in which conducting electrons play a role. In this regard, the absence of magnetism in defected MoS 2 is possibly due to the existence of a sizable band gap; secondly, tensile strain has been proven to be efficient in reducing band gap of pristine single-layer MoS 2 (PMoS 2 ) 11,13 and in improving carrier mobility as well 9,12 .…”
Section: Introductionmentioning
confidence: 99%
“…These ripples can lead to interesting electronic [38][39][40], magnetic [41], and chemical properties [42], mostly due to the associated charge inhomogeneity and the changes in hybridization. In fact, folding graphene has been put forward as a way to modify its properties [43][44][45]; also, folded ribbons have been proposed as graphene-based electronic connectors between edges or graphene layers [46].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In recent years the potential to tune the electronic, [4][5][6][7][8][9][10][11][12] transport, 4,[13][14][15][16][17][18] optical, 10,19,20 and magnetic [21][22][23][24][25] properties of graphene systems by applying strain has been explored. The degree to which these properties can be tuned is enhanced by the different types of strain that can be applied.…”
Section: Introductionmentioning
confidence: 99%